ON NEWTON-LIKE GUMMEL ITERATIVE SOLUTIONS TO DRIFT- DIFFUSION EQUATIONS - Ithnin Abdul Jalil et al. (Proceedings of ICMSA, 2005)
The one-dimensional carrier transport equations as they apply to thesemiconductor devices are governed by the one-dimensional drift diffusionmodel. It is defined by the Poisson's equation, the electroncontinuity equation and finally the hole continuity equation.